Edukasi Pengelolaan Sampah Organik Dan Anorganik Bagi Masyarakat Dan Anak Sekolah Dasar Di Desa Buruan - Tri Wulandari, Agung Mas; Mahadewi, Kadek Julia (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Community Service is a form of activity with research content that places students outside the campus and invites students to think critically so that they can help develop potential in the community with the help of lecturers in solving solutions. Buruan Village, located in Tabanan-Bali Regency, has classic problems in the management of inorganic and organic waste. A waste management system that utilizes vacant land is an option because of the unavailability of waste management methods. The dedication carried out then made a program carried out in Buruan Village in the form of making biopores, recycling plastic or inorganic waste into crafts that are of selling value, and the introduction of the Waste Bank for the community is a form of education to the community in Buruan Village and also for elementary school children to improve students' knowledge and skills in managing plastic waste into source-based waste.            Keywords: organic and inorganic waste; waste bank; waste recycling